Engenharia didática reversa como um dispositivo de formação docente para a educação do campo - SILVA, Renata Lourinho da (Universidade Federal do Pará, 2022)
This research proposes the reverse didactic engineering methodology as educational formation device for field education with purpose of building answers for the integration problems of knowledge discipline with field non knowledge discipline, under study course understanding and research as development methodology of didactic transposition processes and, in consequence, as ways provider of teacher formation under theory understanding of Yves Chevallard’s didactic transposition. The importance of relating the school timing with the community timing in an integrated way, it is also considered necessary and fundamental for the initial and continuous formation teachers courses for field education, by constituting one of the bases that stands field education, according to the Operational Guidelines for Basic Education in Field Schools (DEOBEC) when it emphasizes the difference of teaching for field education from other regular teachings. A research about the usage of "matapi" was accomplished involving teachers in continuous formation, two "matapi" producers from Pacuí de Cima community, in Cametá, besides the study and investigation directors. The reached results are exciting for the accomplishment of future researches, considering that they confirm the hypotheses for the case of the accomplished research because it shows that the school timing with the community timing unit in one, which is the study timing, by the integration of cultural knowledge, which as, knowledges discipline (mathematics, portuguese, geography, science, and others). All in knowledge reconstruction pointed out didactic transposition process, just as we contribute with the community sustainable development. Besides, the results indicate that the methodology of the reverse didactic engineering can also be used in all courses of teacher formation.